(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Motorcycles are one of the most widely used travel modes in many developing countries, and therefore motorcycle crashes are more dangerous than other vehicles, as for every mile traveled by vehicles, the rate of motorcycle crashes increases. Therefore, many factors contribute to increasing the rate of injuries, including not following safety rules, such as wearing a helmet, exceeding the permitted speed, using things that distract the leg, drinking alcohol, and other factors that help increase the rate of injuries. Motorcycle crashes remain a significant public health concern worldwide, with severe consequences for riders and other road users. Understanding the factors contributing to the severity of motorcycle crashes is crucial for developing effective interventions to reduce their impact. This study presents a scientometric analysis aimed at identifying and synthesizing the key factors associated with the severity of motorcycle crashes. Through a systematic review of the literature using scientometric techniques, including co-occurrence analysis and citation analysis, we examined trends, patterns, and relationships among factors influencing crash severity. Our analysis revealed several prominent factors contributing to the severity of motorcycle crashes, including rider characteristics (e.g., age, experience), environmental factors (e.g., road conditions, weather), vehicle-related factors (e.g., type of motorcycle, helmet use), and behavioral factors (e.g., speeding, alcohol impairment). Additionally, we identified emerging areas of research, such as the influence of advanced safety technologies and the impact of urbanization on motorcycle crash severity.